Thin film composite type positively charged nanofiltration membrane for separation of aqueous streams and nuclear effluents. (19th May 2011) - Dey, T.K.; Bindal, R.C.; Prabhakar, S.; Tewari, P.K.
Thin film composite type positively charged nanofiltration membrane developed by in situ polymerisation of functionalised polyethyleneimine and acid chloride has been used in various aqueous stream separations. The membrane contained fixed quaternary ammonium moieties which contributed to its positive charge. The membrane was tested for its performance in single solute feed systems containing salts of various combinations of univalent and bivalent ions (NaCl, Na2 SO4, CaCl2 and MgSO4 ) in test cells as well as spiral module where it gave differential separation profile for these solutes with high rejection for CaCl2 and low rejection for Na2 SO4 . The 2512 spiral module of the membrane was further used for separation of a simulated effluent solution containing uranyl nitrate, which is a common effluent generated in the nuclear industry. The membrane gave a high separation for uranyl nitrate and low separation for ammonium nitrate indicating that both the solutes can be fractionated by the membrane when they are present together in the nuclear effluent.